Implementasi Mengenai Disiplin PNS Berdasarkan PP No. 53 Tahun 2010 di Biro Kepegawaian Setda Provinsi Jawa Tengah - Marini Ina Safitri; yuwanto .; ahmad taufiq (Journal of Politic and Government Studies, 2014)
Implementation of discipline in the Bureau of Personnel, Central Java Regional Secretariat seen that there are still employees who do not carry out their duties according to established standards. In addition there's also an employee who came late, lack of discipline, playing games, eating his lunch before the specified hours, go home before work, and many employees were chatting during working hours, in addition to employees who often went out of the office during working hours for personal gain, so the effect on the performance of employees in the Bureau of Personnel Secretariat of Central Java province.Organization and Personnel Bureau has the function as in Article 194, among others, the task of policy formulation pelaksanaann area in the field of organization and staffing, and staffing, coaching and facilities in the field of local governance and staffing organization. The method used in this research is descriptive / qualitative qualitative outline of the implementation of the work discipline. The data collection was done by in-depth interviews to several informants representative and obtained documentation.The results of this study show that implementation of the discipline of civil servants under Regulation 53 of 2010 on the Organisation and Personnel Bureau is still considered quite necessary improvements, in terms of discipline comply with working hours is still not good, the sanctions imposed on the Bureau Orpeg it is still not up to the right target. It is based are still many employees who violate discipline and barriers that exist towards discipline in this Orpeg Bureau is a lack of awareness of each employee other than the individual or sanctions given also that the half-formed restrain discipline.Recommendations can be taken the following steps to implementation constraints Discipline Rule 53 of 2010 regarding the government's need for socialization to discipline employees, to make changes in the discipline necessary to re reshuffle the available sanctions in violation kedisiplian and well intesnsif approach between superiors and subordinates in order to create a conducive working atmosphere. Keywords: Implementation, PNS Discipline.